2009
DOI: 10.1158/0008-5472.can-08-4151
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Cancer Cell Detachment and Multicellular Aggregate Formation Are Regulated by Membrane Type 1 Matrix Metalloproteinase: A Potential Role in I.p. Metastatic Dissemination

Abstract: An early event in the metastasis of epithelial ovarian carcinoma is shedding of cells from the primary tumor into the peritoneal cavity followed by diffuse i.p. seeding of secondary lesions. Anchorage-independent metastatic cells are present as both single cells and multicellular aggregates (MCA), the latter of which adhere to and disaggregate on human mesothelial cell monolayers, subsequently forming invasive foci. Although this unique metastatic mechanism presents a distinct set of therapeutic challenges, fa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(107 citation statements)
references
References 48 publications
7
100
0
Order By: Relevance
“…Indeed less "classical" inflammatory mediators such as hypoxia, HIF-2b, Wnt family members, or epigenetic changes in DNA methylation may well serve as dominant players in the control of MT1-MMP expression or activity in RA (64)(65)(66)(67)(68)(69). Nevertheless, given the expression of MT1-MMP within RA synoviocytes at sites of tissue damage in vivo, its pathophysiologically relevant functional properties, and the recent development of MT1-MMP-specific inhibitors (70), the proteinase could serve as an important target for therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed less "classical" inflammatory mediators such as hypoxia, HIF-2b, Wnt family members, or epigenetic changes in DNA methylation may well serve as dominant players in the control of MT1-MMP expression or activity in RA (64)(65)(66)(67)(68)(69). Nevertheless, given the expression of MT1-MMP within RA synoviocytes at sites of tissue damage in vivo, its pathophysiologically relevant functional properties, and the recent development of MT1-MMP-specific inhibitors (70), the proteinase could serve as an important target for therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Implantation of spheroids on the peritoneum involves interactions between cancer cells and the mesothelium. Adhesion of ovarian cancer cells to the mesothelial layer is facilitated by the expression of matrix metalloproteinase such as MMP-2 and MMP-9, and by ibronectin and vitronectin as well as their integrin receptors [67][68][69]. Once tumor cells have atached to the peritoneal surface, they gain access to the submesothelial environment by exerting force on the mesothelial lining, driving migration and clearance of the mesothelial cells [70].…”
Section: How Does the Tumor Environment Afect Eoc Dissemination?mentioning
confidence: 99%
“…Laminin-5 and Collagen Type I Attenuate MT1-MMP-induced Cellular Aggregation-Prior studies have demonstrated that MT1-MMP can affect cellular behavior by cleaving integrins from the cell surface (47,51,52). Therefore, we induced MT1-MMP in SCC25 cells and used FACS analysis to examine subsequent effects on the relative cell surface levels of ␤1-, ␣2-, and ␣3-integrins.…”
Section: Induction Of Mt1-mmp Promotes Cellular Aggregation Inmentioning
confidence: 99%